To simplify the expression \((4^3 \cdot 7^{-2})^{-5} / (7^9 \cdot 4^{-13})\), we'll start by applying the properties of integer exponents.
Step 1: Simplify the Numerator
We begin with the numerator \((4^3 \cdot 7^{-2})^{-5}\): \[ (4^3 \cdot 7^{-2})^{-5} = (4^3)^{-5} \cdot (7^{-2})^{-5} \] Using the property \((a^m)^n = a^{m \cdot n}\): \[ = 4^{-15} \cdot 7^{10} \]
Step 2: Rewrite the Expression
Now substituting back into the expression, we have: \[ \frac{4^{-15} \cdot 7^{10}}{7^9 \cdot 4^{-13}} \]
Step 3: Apply the Quotient Rule
Using the quotient rule of exponents, \(a^m / a^n = a^{m - n}\): \[ = \frac{4^{-15}}{4^{-13}} \cdot \frac{7^{10}}{7^9} \] Calculating each term: \[ = 4^{-15 - (-13)} \cdot 7^{10 - 9} \] This simplifies to: \[ = 4^{-2} \cdot 7^1 \]
Step 4: Rewrite with Positive Exponents
To express \(4^{-2}\) with positive exponents: \[ 4^{-2} = \frac{1}{4^2} = \frac{1}{16} \] Thus, we rewrite our expression: \[ = \frac{1}{16} \cdot 7 = \frac{7}{16} \]
Final Answer
So, the simplified fraction with no remaining exponents is: \[ \boxed{\frac{7}{16}} \]